أثر التحول الرقمي على الثقافة التنظيمية لدى مؤسسات التعليم العالي الليبية (Comprehensive Journal of Science, 2025)
This study aimed to investigate the impact of digital transformation on organizational culture within Libyan higher education institutions. It also sought to clarify the concepts of digital transformation and organizational culture, and to understand the nature of their relationship, The researchers employed a descriptive-analytical approach, using a questionnaire as the primary data collection tool. Due to the large population size, a simple random sample of 183 employees and faculty members from Libyan higher education institutions was selected. The questionnaire was created and distributed via Google Forms to ensure broad geographical coverage. Data analysis was conducted using SPSS statistical software.